Pengembangan Media Pembelajaran Pop Up Book Pelajaran Matematika di Sekolah Dasar - Lutfiyyah Indah Permata Sari; Ramanata Disurya; Tanzimah (Jurnal Lensa Pendas, 2025)
This research aims to produce Pop Up Book learning media for Mathematics learning that is valid, practical and effective/has potential effects. The model used in the research is the ADDIE model (Analyze, Design, Development, Implementation and Evaluation). The results of data analysis show that the Pop Up Book developed is in the "very valid" category based on the expert validation questionnaire sheet, namely language experts, material experts, media experts with an average validity value of 86.2%, Pop Up Book. The book developed is included in the "very practical" category based on the One to One and Small Group trial questionnaire sheets with an average practicality score of 85.7% and the Pop Up Book developed in the "Very Effective" category based on the total number of students' completeness scores with an average score effectiveness of 93.1%. Based on the results of validation, trials and student completion scores, it can be concluded that this Pop Up Book product is suitable for use as a learning medium for Mathematics learning in elementary schools.